METODE PEMBELAJARAN AL-QUR’AN MELALUI MAJLIS TARBIYATUL QUR’AN UNTUK MENINGKATKAN BACAAN AL-QUR’AN DI PONDOK PESANTREN MIFTAHUL ULUM ATTHOHIRIN GONDANGLEGI MALANG - Revita Lovinary; Imam Athoir Rokhman (STAI Ma'had Aly Al-Hikam Malang, 2023)
Education is the main foundation that can develop human resources and make one of the platforms for Indonesian people to learn. In the world of education it is not enough to learn formal science, so we must learn knowledge based on religious education. Especially students must be taught the knowledge of the Qur'an, because the Qur'an is a form of Islamic shi'ar to strengthen and strengthen aqidah and faith. Pesantren Miftahul Ulum Atthohirin is a Qur'anic educational institution that aims to boost Islamic boarding schools to give birth to a good generation based on the Qur'ani. This study used qualitative descriptive research with a type of field research. As for how to solve problems with interviews, observation, and documentation. Data reduction, data presentation, and verification or drawing conclusions are data analysis techniques used in this study. The results showed that: (1) The Qur'an learning method at MTQ Miftahul Ulum Atthohirin Islamic Boarding School includes planning, implementing and evaluating learning. (2) The supporting factors of MTQ Miftahul Ulum Atthohirin Islamic Boarding School are the provision of learning media and the provision of activities outside the classroom. While the inhibiting factor is that students do not meet the achievement target and not all students have a cellphone or laptop when conducting the exam at the end of the semester.